PENERAPAN WEBSITE E-COMMERCE SEBAGAI MEDIA TRANSAKSI PADA PERGURUAN TINGGI - Hariguna, Taqwa; Aini, Qurotul; Fitriani, Radifa Rahma (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
Rapid technological advancements provide many conveniences, including the ease of buying and selling activities. At Raharja College there is a sale and purchase transaction facility, Raharja Internet Cafe (RIC), which is provided to meet the needs of its students. In this facility there are print, scan, ATK, accesoris, computer and even install iPad services. However, because at this time the transaction process was still conventional where students had to come directly to the RIC to make transactions and had to queue up to be a problem because it was considered less effective. Therefore, an online transaction is needed that will make it easier for students to transact and meet the needs of lecture activities. So in applying online transactions using e-commerce website (electronic commerce) in the process of buying and selling in RIC. In this study will be explained by researchers 2 (two) problems and 4 (four) research methods, namely: observation, analysis, literature study and implementation. The results achieved from this study are an e-commerce website (electronic commerce) that can be used online by students at any time and anywhere, and can be via a computer or even a smartphone. With the implementation of e-commerce web sites, it is expected that students do not need to come directly to RIC and queue to be able to make transactions because they can be accessed online.